Extra-embryonic tissue spreading directs early embryo morphogenesis in killifish - Germán Reig (Nature Portfolio, 2017)
The role of mechanical signals in early development are not fully understood. Here, the authors use the simplicity of early killifish embryos to show that tension arising from extra-embryonic epithelial expansion directs the spreading of mesenchymal-like embryonic cells during early morphogenesis.